Peran Teknologi Artificial Intelligence (AI) dalam Memperkuat Dakwah Islam di Era Digital - Ibnu Waseu (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
In today's digital era, technological development is occurring rapidly and having a significant impact on various aspects of human life, including Islamic da'wah. The transformation of the spread of Islamic teachings in the digital age has become inevitable along with the rapid advancement of information technology, particularly with the advent of Artificial Intelligence (AI). This study aims to explore how AI is utilized in spreading Islamic values and analyze the accompanying ethical and theological challenges. This research uses a qualitative approach with a literature study method, which includes a review of scientific journals, articles, and contemporary Islamic documents. The results show that AI has been applied in various forms of digital da'wah. For example, Islamic chatbots that can automatically answer religious questions, prayer and other worship reminder applications, and Quran learning platforms equipped with voice recognition and tajweed recitation technology. Although innovative and promising, the use of AI in da'wah poses challenges, particularly the threat to authority over scientific knowledge, the validity of religious content, and the risk of dehumanization in the process of conveying Islamic teachings. Therefore, an adaptive yet ethical approach to Islamic preaching is needed, involving collaboration between religious scholars, academics, and technology experts. This approach must take into account the values of Islamic law, morality in digital communication, and sensitivity to the cultural context of Muslims. Thus, AI-based Islamic preaching can be an innovative solution for effectively reaching a wider audience, without sacrificing the essence and spirituality taught by Islam itself. Thus, AI-based Islamic preaching can be an innovative solution for effectively reaching a wider audience, without sacrificing the essence and spirituality taught by Islam itself. Going forward, a sustainable Islamic digital ecosystem needs to be built so that technology becomes not only a tool, but also a means of increasing faith and piety.